Influence of game evolution and the phase of competition on temporal game structure in high-level table tennis tournaments - Vieira de Mello Leite, J.; Barbieri, F. A.; Miyagi, W.; de Souza Malta, E.; Moura Zagatto, A. (Journal of Human Kinetics, 2017)
The aims of this study were: a) to investigate the game temporal structure in high-level table tennis competitions; b) to verify the influence of game evolution in international competitions from 2009 to 2012 (World Table Tennis Championships and the Olympic Games) on game temporal structure; c) to compare game temporal structure according to the phase of competition. Comparisons between the three international tournaments demonstrated that rally duration decreased significantly (p < 0.05) during the analyzed period (2009-2012), while the rest time increased (p < 0.05) from 2009 to 2011, but decreased (p < 0.05) from 2011 to 2012. In the competition phase analysis, it was found that rally duration decreased (p < 0.05) in the quarterfinals in relation to the semifinals and finals, while the rest time increased (p < 0.05) from the quarterfinals to semifinals and finals. Based on our findings and previous literature, we concluded that the performance level, game evolution and the competition phase influenced the game temporal structure of table tennis, considering longer rest periods adopted by elite athletes in relation to non-elite athletes, the reduction in rally duration and an increase in rest time over the 2009-2012 period and through the competition phases (quarterfinals to finals).